P195 Updated Cochrane systematic review: no evidence that vitamin D reduces asthma exacerbations or improves asthma control. (11th November 2022) - Williamson, AE; Griffiths, CJ; Sheikh, A; Martineau, AR
Abstract : Introduction: A 2016 Cochrane review on vitamin D for the management of asthma 1 suggested a role in reducing exacerbations, yet debate has continued with subsequent randomised controlled trials reporting inconsistent findings. Objectives: To evaluate the efficacy of administration of vitamin D and its hydroxylated metabolites in reducing the risk of asthma exacerbations and improving asthma symptom control. Methods: We searched the Cochrane Airways Group Register for double-blind randomised placebo-controlled trials of vitamin D or its hydroxylated metabolites in children and adults with asthma from the beginning of records until November 2021. Four authors independently evaluated study eligibility, extracted data, and assessed risk of bias. Results: Administration of vitamin D did not influence the proportion of participants experiencing one or more asthma exacerbations treated with systemic corticosteroids (primary outcome; odds ratio [OR] 0.99, 95% confidence interval [CI] 0.77 to 1.27; 1709 participants, 14 studies; high-quality evidence) or any secondary efficacy outcome, including Asthma Control Test score (mean difference 0.74 points, 95% CI -0.20 to 1.68, 1303 participants; 8 studies; moderate-quality evidence). Vitamin D did not affect the proportion of participants experiencing one or more serious adverse events (OR 0.89, 95% CI 0.56 to 1.41; 1541 participants, 12 studies; high-quality evidence), Sub-group analysis did not reveal any evidence of effect modification by baseline vitamin D status, vitamin D dose, or age. A single trial investigating administration of calcidiol (25-hydroxyvitamin D3 ) reported a benefit of the intervention for the primary outcome of asthma control. Conclusions: This systematic review does not find evidence to support a role for vitamin D supplementation to reduce risk of asthma exacerbations or improve asthma control. Participants with severe asthma and those with baseline 25(OH)D concentrations <25 nmol/L were poorly represented, and a protective effect of the intervention cannot be excluded in these groups. A single study investigating effects of calcidiol yielded positive results; further studies investigating effects of this metabolite are needed. Reference: Martineau AR, Cates CJ, Urashima M, Jensen M, Griffiths AP, Nurmatov U, Sheikh A, Griffiths CJ. Vitamin D for the management of asthma. Cochrane Database of Systematic Reviews 2016, Issue 9. Art. No: CD011511. Please refer to page A215 for declarations of interest related to this abstract.